Wear, friction and profilometer studies of insitu AA5052/ZrB2 composites - Kumar N.; Gautam G.; Gautam R.K.; Mohan A.; Mohan S. (My University, 2025)
Wear studies of insitu AA5052/ZrB2 composites show a linear relationship between cumulative wear and sliding distance, whereas, coefficient of friction has fluctuating tendency. Wear rate and coefficient of friction continuously increase with sliding velocity and load showing mild to severe transition at higher values. Amount of ZrB2 also affects the wear and friction behaviour. The worn surface study and EDS analysis are in agreement with wear and friction results. Morphology and mechanical properties have also been correlated with wear and friction. These composites could be potential candidate in applications like brake drums/rotors, cylinder liners, connecting rods, cylinder blocks and pistons. © 2016 Elsevier Ltd. All rights reserved.